Significant perpendicular magnetic anisotropy in room-temperature layered ferromagnet of Cr-intercalated CrTe2. (5th May 2021) - Huang, Meng; Ma, Zongwei; Wang, Sheng; Li, Si; Li, Miao; Xiang, Junxiang; Liu, Ping; Hu, Guojing; Zhang, Zengming; Sun, Zhe; Lu, Yalin; Sheng, Zhigao; et al.
Abstract: Magnetic anisotropy is an important characteristic of magnetic materials. Particularly, perpendicular magnetic anisotropy (PMA) is superior for the design of spintronic devices, with the advantages of scalability, endurance, thermal stability, and low switching current density. Although a series of two-dimensional (2D) or quasi-2D layered ferromagnets have been demonstrated, the room temperature intrinsic ferromagnets with PMA is rarely found. Here, we report PMA in a room-temperature layered ferromagnet of Cr-intercalated CrTe2 . By self-intercalation of the native Cr atoms, the in-plane anisotropy of CrTe2 can be switched to PMA. Meanwhile, the Cr-intercalated CrTe2 crystal can be easily exfoliated into thin flakes with thickness ∼10 nm. Besides the robust PMA at room temperature, Cr-intercalated CrTe2 also exhibits high saturation magnetization (208 emu cm −3 at 300 K), large anomalous Hall angle (2.23% at 300 K) and giant anomalous Hall factor (∼0.18 at 300 K). These excellent properties are highly desired for applications, and make Cr-intercalated CrTe2 a distinguished candidate among all existing magnetic materials. Our work reveals a promising platform for spintronic devices and offers a new route for controlling the magnetic anisotropy in layered materials.